Atuação do Conselho Nacional de Justiça e independência jurisdicional: interfaces e interferências - Moreira, Diogo Rais Rodrigues (2015)
Is it possible to identify zones of accommodation and conflict between the activity of the Conselho Nacional de Justiça (CNJ National Council of Justice) and jurisdictional independence? What constitutes these zones? How can they be categorized? The aim of this thesis is to seek answers to these and other questions. Our research is based on the assumption that jurisdictional independence should not be an insurmountable obstacle to the activity of the CNJ, nor should the Council s activity bring about the end of jurisdictional independence. Therefore, this research follows a central thread formed by a series of questions related to the national judiciary branch and the insertion of the Conselho Nacional de Justiça in its structure. We address the relation between jurisdiction and non-jurisdiction and the protection of jurisdictional independence through international norms and through the Brazilian Constitution, with the specific aim of presenting definitions of judicial and jurisdictional independence. We then analyze the decisions of the Conselho Nacional de Justiça that directly address jurisdictional acts. This analysis was based on an initial list of 2.750 normative and disciplinary acts issued by the Conselho Nacional de Justiça, of which only those specifically aimed at jurisdictional decisions were selected. This selection was then organized and categorized according with common features and results found in the acts, leading to the creation of the categories herein referred to as zones of interface and interference. Lastly, the results of the research are interpreted in the light of the definition of jurisdictional independence herein adopted. We thus seek to offer some conclusions about the relationship between the activity of the Conselho Nacional de Justiça and jurisdictional independence, either by means of an interface zone or through direct interference